Predication at the interface - Åfarli, Tor A.; Eide, Kristin M. (ZAS Papers in Linguistics, 2001)
We try to show that predication plays a greater role in syntax than commonly assumed. Specifically, we wil argue that predication to a large extent determines both the phrase structure of clauses and trigger syntactic processes that take place in clauses. If we are on the right path, this implies that syntax is basically semantically driven, given that predication is semantically construed.